Endodontic treatment in patients previously subjected to head and neck radiotherapy: a literature review - Yanaguizawa, Wellington Hideaki; Kobayashi-Velasco, Solange; Gialain, Ivan Onone; Caldeira, Celso Luiz; Cavalcanti, Marcelo Gusmao Paraiso (Journal of Oral Diagnosis, 2019)
The head and neck region is an expressive site of malignant neoplasms. Radiation therapy is a type of cancer treatment that can be used before or after surgical procedures, or in contraindicated surgery cases. Radiotherapy can cause various side effects in the patient’s mouth, including xerostomia, mucositis, radiation cavities, and osteoradionecrosis. Due to the risk of osteoradionecrosis after dental extractions, endodontic treatment ends up being the best preventive and therapeutic method. The purpose of this study is to review the literature on endodontic treatment in cancer patients undergoing radiotherapy.